Teachers’ Use of Code Switching in An English as a Foreign Language Context in Indonesia - Suganda, Lingga Agustina; Loeneto, Bambang A; Zuraida, Zuraida (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This study proposed to investigate the phenomena of code switching which refers to the use of English and Indonesian as a medium of instruction used by the English as a Foreign Language (EFL) teachers in their classroom discourse. It depicted the attitudes of EFL teachers and their students towards the patterns, functions, and influence of code switching in two EFL classes in Indonesia. The data were collected from classroom observation, interview, and questionnaire which explored the occurrence of code switching during the teaching and learning process as well as the teachers and students’ perception on its use in the classroom context. The results indicated that the switching between English and Indonesian in the EFL classrooms was very natural since it also became a tool to show the cultural, social, and communicative aspects of each language despite the amount of its use which varied greatly from teacher to teacher due to their students’ English competence.